Integration of Gold Nanoparticles into NIR‐Radiation Curable Powder Resin. Issue 17 (28th October 2016) - Schmitz, Christian; Gökce, Bilal; Jakobi, Jurij; Barcikowski, Stephan; Strehmel, Bernd
Abstract: Gold nanoparticles were integrated into a maleate polyester/vinylurethane powder coating by mixing the prepolymer with a colloid comprising either tetrahydrofurane or tripropyleneglycoldiacrylate as continuous phase. This slurry was extruded resulting in a homogeneous distribution of nanoparticles in the resin. Curing of the powder coating occurred by near infrared (NIR) photopolymerization. The initiator system comprised the heptamethine cyanine absorberS2265 and bis‐(4‐( t ‐butyl)‐phenyl)iodonium bis(trifluoromethylsulfonyl)imide as radical initiator. The use of NIR‐LED arrays as a light source for photopolymerization of the powder coating is insufficient due to the low emission intensity. In addition, absorption and scattering of nanoparticles prevent penetration of excitation light in deeper layers of the molten coating. This avoids curing of deep layers in the curing sample. Nevertheless, exposure with IR radiators results in high conversions of cured powder resin even if nanoparticles were embedded. Such treatment also gives the possibility for simultaneous melting and spreading of the powder coating on the substrate resulting in a solidified film nearly by one process step. This new procedure demonstrates the facile integration of nanoparticles with plasmon resonance in the visible region into the solidified and filmed powder coating. Abstract : Nanoparticle fabrication by laser ablation and embedding in powder coatings results in functionalized surfaces by curing with NIR light